2020
DOI: 10.1177/0300060520948337
|View full text |Cite
|
Sign up to set email alerts
|

Is electroacupuncture safe and effective for treatment of stress urinary incontinence in women? A systematic review and meta-analysis

Abstract: Objective Stress urinary incontinence (SUI) is prevalent worldwide, particularly among elderly women. Although electroacupuncture (EA) has been accepted by many patients and physicians in Asia, its efficacy for SUI has not been evaluated scientifically and systematically. We aimed to conduct a systematic evaluation of the efficacy and safety of EA treatment for women with SUI. Methods We retrieved publications up to February 2019 from seven databases. Randomized controlled trials for women with SUI treated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…According to this review, ICIQ-SF scores increased, and 1-h urine leakage decreased in patients who underwent electroacupuncture compared with those receiving sham electroacupuncture, physical exercise, or medication. 11 As a result, the present study has exciting results, and promising evidence is accumulating that acupuncture can be effective in the treatment of UI. The results also can contribute to understanding the acupuncture treatment's modulation effect in UI.…”
mentioning
confidence: 74%
“…According to this review, ICIQ-SF scores increased, and 1-h urine leakage decreased in patients who underwent electroacupuncture compared with those receiving sham electroacupuncture, physical exercise, or medication. 11 As a result, the present study has exciting results, and promising evidence is accumulating that acupuncture can be effective in the treatment of UI. The results also can contribute to understanding the acupuncture treatment's modulation effect in UI.…”
mentioning
confidence: 74%
“…Regarding the methodological quality of the included SRs/MAs, all were considered to be of very low quality because more than one key item was missing from the SRs/MAs included in the quality assessment. Methodological quality limitations come from the following items: Items 2 (Only 2 SRs/MAs [ 19 , 20 ] registered the research protocol), Item 4 (None of the SR/MA performed a comprehensive literature search), Item 7 (None of the SR/MA provided studies excluded from the list), and Item 10 (None of the SR/MA reported the funding of RCTs included in SRs/MAs). The evaluation details of the included SRs/MAs on the AMSTAR-2 are shown in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In Domain 3, 6 SRs/MAs [ 18 – 22 , 25 ] were rated as low risk of bias. Domain 4 assessed the synthesis and findings, and only 2 SRs/MAs [ 19 , 23 ] were rated as low risk of bias. Phase 3 considered the overall risk of bias in the reviews, and none of the SR/MA had a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have suggested acupuncture to be a safe intervention for pediatric CP with no serious adverse event reported ( 6 , 45 , 46 ). Although there are no reports on the safety of EA in the treatment of CP yet, studies have confirmed its great safety on other neurological disorders ( 47 49 ). There are few studies comparing EA with other pharmacologic or invasive intervention.…”
Section: Discussionmentioning
confidence: 99%